2013
DOI: 10.1016/j.brainres.2013.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of the neuropeptide somatostatin on methamphetamine and glutamate-induced neurotoxicity in the striatum of mice

Abstract: A large body of evidence shows that methamphetamine (METH) causes sustained damage to the brain in animal models and human METH users. In chronic users there are indications of cognitive and motor deficits. Striatal neuropeptides are in a position to modulate the neurochemical effects of METH and consequently striatal neural damage. Somatostatin (SST) is an intrinsic striatal neuropeptide that has been shown to inhibit glutamate transmission; glutamate is integral to METH toxicity and contributes to nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Our results indicated that pretreatment with the selective SST‐depleting agent cysteamine or using an SST receptor antagonist, such as c‐SOM, to some extent, reversed the effects of CAP, illustrating that the endogenous SST released into circulation played effective roles in anti‐inflammation and neuroprotection. Many studies have established that exogenous SST or synthetic analogues exert anti‐inflammatory and/or neuroprotective effects . Szolcsanyi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicated that pretreatment with the selective SST‐depleting agent cysteamine or using an SST receptor antagonist, such as c‐SOM, to some extent, reversed the effects of CAP, illustrating that the endogenous SST released into circulation played effective roles in anti‐inflammation and neuroprotection. Many studies have established that exogenous SST or synthetic analogues exert anti‐inflammatory and/or neuroprotective effects . Szolcsanyi et al.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,29 Many studies have established that exogenous SST or synthetic analogues exert anti-inflammatory and/or neuroprotective effects. 11,[33][34][35][36][37] Szolcsanyi et al found for the first time that the mediator SST could release not only locally but also systemically from CAP-sensitive afferent fibres. 7,9 An electrical stimulation (20 v, 0.5 ms, 5 Hz for 5 minutes), which was fit for the activation of the C fibres, may diminish the contralateral limbs' plasma extravasation by 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in glutamate in the striatum and hippocampus are known to correlate with increases in glutamate levels during Meth exposure. Recently, it was shown that somatostatin, which is a known inhibitor of glutamate neurotransmission, has the ability to reduce Meth-induced cell death in the striatum (Afanador et al, 2013). The decrease in the number of parvalbumin in the hippocampus of MDMA treated rats has been linked to the increases in extracellular glutamate and cyclooxygenase activity observed during MDMA exposure (Anneken et al, 2013).…”
Section: Mechanisms Of Neurotoxicitymentioning
confidence: 99%
“…The same population of striatal interneurons making NPY also makes the neuropeptide somatostatin [41]. Our laboratory recently reported that somatostatin also counters the damaging effects of METH protecting the striatal neurons from the METH-induced apoptosis [1]. Thus, neuropeptides represent endogenous agents expressed and utilized in the healthy striatum that modulate dopaminergic responses under physiological homeostatic conditions as well as in aberrant states involving a surfeit of dopamine such as induced by METH.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the striatal neuropeptide substance P synergizes with METH in elevating the production of nitric oxide [64] and consequently striatal injury [73]. Interestingly, two other striatal neuropeptides, somatostatin and neuropeptide Y, attenuate the METH-induced striatal production of nitric oxide [1,69]. In addition to endogenous agents such as neuropeptides, it is advantageous to identify exogenous substances that ameliorate oxidative stress and thus could be neuroprotective in the presence of METH.…”
Section: Introductionmentioning
confidence: 99%